2008
DOI: 10.1152/ajplung.00069.2008
|View full text |Cite
|
Sign up to set email alerts
|

TTF-1 response element is critical for temporal and spatial regulation and necessary for hormonal regulation of humansurfactant protein-A2promoter activity

Abstract: Liu D, Yi M, Smith M, Mendelson CR. TTF-1 response element is critical for temporal and spatial regulation and necessary for hormonal regulation of human surfactant protein-A2 promoter activity. Am J Physiol Lung Cell Mol Physiol 295: L264 -L271, 2008. First published May 16, 2008 doi:10.1152/ajplung.00069.2008.-Expression of the human surfactant protein-A2 (hSP-A2) gene is lung specific, occurs in type II and Clara cells, and is developmentally and hormonally regulated in fetal lung. Using transfected human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…In studies using transgenic mice and transfected type II cells, we observed that a 300-bp region upstream of the rabbit [7679] and human [8086] SP-A genes is critical for lung cell-specific, developmental and cAMP/IL-1β-induced expression (Fig. 3).…”
Section: Fetal Signals Leading To the Initiation Of Parturitionmentioning
confidence: 99%
“…In studies using transgenic mice and transfected type II cells, we observed that a 300-bp region upstream of the rabbit [7679] and human [8086] SP-A genes is critical for lung cell-specific, developmental and cAMP/IL-1β-induced expression (Fig. 3).…”
Section: Fetal Signals Leading To the Initiation Of Parturitionmentioning
confidence: 99%
“…In studies using transgenic mice (19,20) and transfected type II cells (21)(22)(23)(24)(25), we found that as little as approximately 300 bp of SP-A 5Ј-flanking sequence mediates lung cell-specific, developmental, and cAMP-regulated expression. This region contains four response elements that are highly conserved in the SP-A genes of various species (26).…”
mentioning
confidence: 94%
“…In recent studies using transgenic mice carrying fusion genes comprised of various amounts of 5Ј-flanking sequence from the hSP-A2 gene fused to hGH, as reporter, we observed that as little as 175 bp of hSP-A2 5Ј-flanking DNA promoted appropriate developmental and lung cell-specific expression. However, the 175-bp genomic region (which lacks the ERRE) was insufficient to mediate cAMP regulation of SP-A promoter activity (20). Collectively, these findings suggest that ERR␣ is an important mediator of SP-A gene expression and its induction by cAMP.…”
mentioning
confidence: 95%
“…Additionally, the ATP-binding cassette, subfamily A, member 3 (ABCA3), an essential transporter that mediates surfactant lipoprotein trafficking and lamellar body biogenesis (32,33), showed only modest, nonsignificant changes in lungs of SRC-1/-2 double-deficient fetuses (Supplemental Figure 1C). hormonal regulation of expression (18,19). Steroid receptor coactivators 1 and 2, SRC-1 and SRC-2, serve important roles in transcriptional upregulation of SP-A gene expression in fetal lung type II cells (20,21).…”
Section: Introductionmentioning
confidence: 99%